PENGARUH PENGGUNAAN MASKER KACANG HIJAU TERHADAD PERAWATAN KULIT WAJAH KERING - Nella, Agusri; Rostamailis, Rostamailis; Yanita, Merita (Journal of Home Economics and Tourism, 2017)
This study aimed to analyze the effect of using a mask of green beans to dry facial skin care. This study is based on indicators of the level of skin moisture changes. This study is quasi experiment with nonequivalent control group design. The object of this study is a student at the State University of Padang, while the sample in this study were female students aged 19-25 years who have dry skin types. Data collected from this study are primary data obtained directly from the sample by filling out the assessment format has been provided. The data were analyzed using normality test, homogeneity and t test. Based on the results of the data, proving that mask use green beans showed a significant result on the indicator with the result of the normality test large numbers (0.796)> Î± = 0,05 means the normal distribution of data, results of homogeneity test with a score of 0.398 > Î± = 0,05 and continued with the t test results with the results of 3,157 t > ttable 2,060. This means that there is a significant effect on facial skin care with the use of masks green beans.Keywords : Green beans, Dry facial skin care.